The Effect Of Wordsearch Puzzle Game On English Vocabulary Mastery At Seventh Grade Of SMP Swasta Mars Pematangsiantar: English - Sitanggang, Nikita Gabriela; Munthe, Melda Veby Ristella; Anggita Situmeang, Siska; Jesica Sitanggang, Yolanda (Universitas Pahlawan Tuanku Tambusai, 2024)
The researcher decided to apply wordsearch games in this study. The purpose of this study was to determine the effect of using hidden word games on English vocabulary skills in grade seven of Mars Pematangsiantar Private Junior High School in the 2023/2024 school year. This study used a quasi-experimental design with quantitative methods. In this study, researchers used two classes, namely the experimental class and the control class. Researchers took the population of class VII with a total of 50 students. For the sample, the number of students taken was the same in the experimental and control classes, namely 25 students. The sample for the experimental class was class VII-A and the sample for the control class was class VII-B. Students were selected using purposive sampling technique. To analyze the data, the researchers used the t-test formula to determine whether the use of wordsearch games affects the mastery of English vocabulary. After analyzing the data, the results of this study showed the average pre-test and post-test scores of the experimental class and the average pre-test and post-test scores of the control class. In the experimental class, the mean pre-test score was 55.6 and the mean post-test score was 76. In the control class, the mean value of the pre-test was 60 and the mean value of the post-test was 69.4. The standard deviation for the experimental class was 5.746 and the standard deviation for the control class was 666. After calculating the average value and standard deviation of the two classes, the researcher calculated using the t-test formula, the t-count result was greater than the t-table with a significance level of 5% (3.374> 1.677). Based on these results, the researcher concluded that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. Therefore, it can be concluded that the use of Wordsearch puzzle game has an effect on English vocabulary acquisition, especially in grade seven.